2010
DOI: 10.1002/hep.23574
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analyses and Transcriptomic Profiling of Circulating Messenger Rnas As Biomarkers of Rat Liver Injury

Abstract: Serum aminotransferases have been the clinical standard for evaluating liver injury for the past 50-60 years. These tissue enzymes lack specificity, also tracking injury to other tissues. New technologies assessing tissue-specific messenger RNA (mRNA) release into blood should provide greater specificity and permit indirect assessment of gene expression status of injured tissue. To evaluate the potential of circulating mRNAs as biomarkers of liver injury, rats were treated either with hepatotoxic doses of D-(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 37 publications
6
57
0
Order By: Relevance
“…S3C). Although direct comparisons across model systems are difficult because of variation in experimental design, the results presented are broadly comparable with prior observations in murine models of APAP toxicity (7,(18)(19)(20)(21)(22), indicating conservation of the xenobiotic response.…”
supporting
confidence: 80%
“…S3C). Although direct comparisons across model systems are difficult because of variation in experimental design, the results presented are broadly comparable with prior observations in murine models of APAP toxicity (7,(18)(19)(20)(21)(22), indicating conservation of the xenobiotic response.…”
supporting
confidence: 80%
“…A few publications have paved the route to success, which promises to be labor-intensive (Wetmore et al 2010). In this endeavor, the collaborative consortia across the pharmaceutical industry and academia have a critical role (Roberts 2009).…”
Section: Resultsmentioning
confidence: 99%
“…However, in bupivacaine-treated rats, the levels of aminotransferase activity increased significantly in blood. 67 This demonstrated the specificity of using mRNA-based biomarkers over traditional aminotransferase (protein)-based biomarkers to detect DILI.…”
Section: Rna Markersmentioning
confidence: 98%
“…Several studies have already demonstrated the usefulness of using specific DNA or RNA sequences in the circulation, such as transcripts highly enriched in the liver, as markers to reflect DILI. 11,67,91 The concentrations of these molecules are too low to conduct a global survey using traditional nucleic acid profiling approaches like microarray. Besides microRNA, due to its small repertoire, no systematic survey of the DNA or RNA spectrum in the circulation has been done.…”
Section: Approaches For New Biomarker Discoverymentioning
confidence: 99%